The Lithuanian adjective vienatas, -a / vienatis, -ė - Judžentis, Artūras (Baltistica, 2016)
The article analyses the usage, meaning and forms of the adjective vienatas / vienatis used in some Old Lithuanian writings until the 17th century. The primary meaning of the adjective presumably was ‘integral, steady, constantʼ, the meaning ‘the only oneʼ being of later origin. A renewed introduction of the adjective into historical linguistics allows to reconsider some related etymologies.
Keywords: Lithuanian; grammatical category; adjective; semantics; word-formation